The Impact of Child Care Costs on Female Labour Supply: Evidence from Canada - Lisa M. Powell (Queen's University, Department of Economics, 1994)
This paper provides estimates for Canada of the impact of child care costs on female labour supply. This is done by linking two Statistics Canada microdata sources. Specifically, the data used in this paper are from the 1988 National Child Care Survey and the 1988 Monthly (September) Labour Force Survey. The paper provides child care price elasticities for labour force participation for married women and compares the results with those found by U.S. researchers. The paper also provides labour supply elasticities incorporating the effects of child care costs. The results show that the market wage has a significant positive impact on both the mother's labour force participation decision and her hours of work supplied. Child care costs are found to have a significant negative impact on hours of work conditional upon employment and a negative but insignificant impact on labour force participation.
Keywords: 330